2013
DOI: 10.5140/jass.2013.30.3.179
|View full text |Cite
|
Sign up to set email alerts
|

The Photometric Brightness Variation of Geostationary Orbit Satellite

Abstract: Photometric observation is one of the most effective techniques for determining the physical characteristics of unknown space objects and space debris. In this research, we examine the change in brightness of the Communication, Ocean, Meteorological Satellite-1 (COMS-1) Geostationary Orbit Satellite (GEO), and compare it to our estimate model. First, we calculate the maximum brightness time using our calculation method and then derive the light curve shape using our rendering model. The maximum brightness is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Seo et al (2013) showed that the apparent magnitude of the COMS varied between 12 and 16. Additionally, taking into consideration that the average apparent magnitude of the 66 geostationary satellites that are observable from the Korean peninsula is approximately 11, the COMS is a relatively faint satellite.…”
Section: The Campaign Observation Using Wft3mentioning
confidence: 97%
“…Seo et al (2013) showed that the apparent magnitude of the COMS varied between 12 and 16. Additionally, taking into consideration that the average apparent magnitude of the 66 geostationary satellites that are observable from the Korean peninsula is approximately 11, the COMS is a relatively faint satellite.…”
Section: The Campaign Observation Using Wft3mentioning
confidence: 97%
“…In principle, the problem can be reversed, and the satellite's orientation and physical parameters of reflection can be empirically determined from well-sampled multi-colour polarimetric lightcurves (polarisation degree and angle), assuming some basic shape properties and geometry (aided by lightcurve analysis, e.g. Seo et al, 2013) as priors, by fitting a Mueller matrix chain (describing the optical action of each reflecting element) directly onto the total observed wavelengthdependent polarisation as a function of angle. This is a method frequently used in calibration and design of optical telescopes and instruments, where we can fit for the orientation and indices of refraction of reflecting surfaces as free parameters in the components of the Mueller matrix chain made up of all optical components (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because different satellites have different brightnesses, optical photometric observations provide information about a satellite's position, attitude and material properties (Jah & Madler 2007;Hall 2010). Moreover, optical observation is an important method for empirical interpretation and determining the shapes of asteroids (Schildknecht et al 2008;Seo et al 2013). Optical surveys primarily provide statistical information about the environment, including rough characterization of the orbits and brightnesses (magnitude, unit: [ m ]) of objects.…”
Section: Introductionmentioning
confidence: 99%